THE PREVALENCE OF EUSTACHIAN VALVE ON TRANSOESOPHAGEAL ECHO EXAMINATION - Marek, Dan; Sovova, Eliska; Kocianova, Eva (Biomedical papers, 2011)
Background: The Eustachian valve (EV) is an embryonic structure redirecting the blood flow from the inferior vena cava through the foramen ovale. It may persist in adults as a floating membrane in the right atrium. A large EV can be associated with thrombosis, embolization, bacterial endocarditis, etc. The prevalence of EV in the normal population is unknown.Aim: to assess the prevalence and size of EV in unselected patients examined by transoesophageal echo.Methods: 1100 consecutive patients were examined for various reasons by a single operator and interpreter. Routine check was made for the presence of EV in the right atrium. Only patients with a mobile EV and not with a simple rigid rim were counted. Three measurements of the EV length at the level of the aortic valve (i.e. 90°C) were made off-line and the longest distance considered. If the EV was not visualized and recorded as a straight line because of its chaotic movement, the picture of the valve was segmented into several separated valve portions and the sum taken as the true length.Results: 46 patients (24 males) with EV were identified out of total 1100 pts examined. The average length of the EV was 23.6 ± 9.7 mm (7-47 mm, median 23 mm).Conclusions: The finding of a persisting Eustachian valve on transoesophageal echo examination is not rare. The prevalence was similar in men and in women. Bearing in mind the possible complications associated with a large valve, we recommend that a proper description of persistent EV is included in routine transoesophageal echo reports.
Keywords: Eustachian valve/Prevalence/Transoesophageal echocardiography/Complications